Using small numbers of subjects in fMRI-based research. - Savoy, R.L (IEEE Engineering in medicine and biology magazine)
This article reviews a number of issues related to the special features and potentials associated with doing functional brain imaging experiments with one or a small number of subjects. It concludes with a speculation that, ironically, it may someday turn out that the information from a few brains, thoroughly studied, will reveal more about universal aspects of human brain function and organization than the current torrent of studies from large collections of brains.